2019
DOI: 10.1515/gps-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, characterization and antimicrobial activities assessment of fabricated selenium nanoparticles using Pelargonium zonale leaf extract

Abstract: The present study focuses on the biogenic synthesis of selenium nanoparticles (Se NPs) using Pelargonium zonale leaf extract under microwave irradiation. Response surface methodology was used to evaluate the effects of the synthesis parameters, namely amounts of the leaf extract (0.5–2.5 ml) and amounts of the 10 mm sodium selenite solutions (15–65 ml), at constant microwave heating (4 min), on the concentration and particle size of the fabricated Se NPs, optimize the synthesis conditions and verify the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 29 publications
4
58
0
Order By: Relevance
“…Reduction in E. coli and P. aeruginosa cells was also perceived after 24 h. A decrease of 2.46, 2.95 7). It was evident that the maximum killing of E. coli, P. aeruginosa and S. aureus cells with nSe was observed after 12 h. Thus, it can be strongly interpreted that the nSe effectively inhibited the growth of Gram positive and Gram negative bacterial strains in a time dependent manner, thereby highlighting its bacteriostatic effect [59,60].…”
Section: Time Kill Assaymentioning
confidence: 90%
“…Reduction in E. coli and P. aeruginosa cells was also perceived after 24 h. A decrease of 2.46, 2.95 7). It was evident that the maximum killing of E. coli, P. aeruginosa and S. aureus cells with nSe was observed after 12 h. Thus, it can be strongly interpreted that the nSe effectively inhibited the growth of Gram positive and Gram negative bacterial strains in a time dependent manner, thereby highlighting its bacteriostatic effect [59,60].…”
Section: Time Kill Assaymentioning
confidence: 90%
“…The size distribution of the synthesized Se NPs is also shown in Figure 7. However, our previous study on green synthesis of Se NPs using Pelargonium zonale indicated that Se NPs with mean particle size, PDI and zeta potential values of 136 nm, 0.321 and -24.6 mV, respectively were fabricated at obtained optimum synthesis conditions using 1.48 mL Pelargonium zonale leaf extract and 15 mL of Na 2 SeO 3 solution [29]. The obtained results indicated that Aloe vera leaf extract could be effectively synthesized Se NPs with smaller particle size and higher stability, due to high value of the zeta potential, as compared to the Pelargonium zonale leaf extract.…”
Section: Dls Analysismentioning
confidence: 97%
“…Selenium nanoparticles (Se-NPs) were evidenced to possess extra bioactivities and functionalities as potent antioxidant, antibacterial, antifungal and anticancer agents [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of metal NPs, and specifically Se-NPs, was efficaciously achieved using numerous biological reducing agents, including plant extracts, resins and microbial metabolites [13][14][15][16][17][18]. Compared to physicochemical protocols of NP synthesis, biological green synthesis of Se-NPs has elevated eco-friendly, non-toxic and biosafety advantages [10]. From the biological green synthesis agents, the employment of plant extracts in NP synthesis (phytosynthesis) is reported to be a simple, effectual and cost-effective method, compared to other biosynthesis agents involving microorganisms and enzymes [11].…”
Section: Introductionmentioning
confidence: 99%